The juice of fresh leaves of Catharanthus roseus Linn. reduces blood glucose in normal and alloxan diabetic rabbits - Lodagala Srinivas D; Boini Murthy K; Nammi Srinivas; Behara Ravindra Babu S (BMC, 2003)
Abstract Background The leaf juice or water decoction of Catharanthus roseus L. (Apocyanaceae) is used as a folk medicine for the treatment of diabetes all over the world. In the present investigation, the leaf juice of C. roseus has been evaluated for its hypoglycemic activity in normal and alloxan-induced diabetic rabbits. Methods The blood glucose lowering activity of the leaf juice was studied in normal and alloxan-induced (100 mg/kg, i.v.) diabetic rabbits, after oral administration at doses of 0.5, 0.75 and 1.0 ml/kg body weight. Blood samples were collected from the marginal ear vein before and also at 4, 6, 8, 10, 12, 16, 18, 20 & 24 h after drug administration and blood glucose was analyzed by Nelson-Somogyi's method using a visible spectrophotometer. The data was compared statistically by using Student's t-test. Results The leaf juice of C. roseus produced dose-dependent reduction in blood glucose of both normal and diabetic rabbits and comparable with that of the standard drug, glibenclamide. The results indicate a prolonged action in reduction of blood glucose by C. roseus and the mode of action of the active compound(s) of C. roseus is probably mediated through enhance secretion of insulin from the β-cells of Langerhans or through extrapancreatic mechanism. Conclusions The present study clearly indicated a significant antidiabetic activity with the leaf juice of Catharanthus roseus and supports the traditional usage of the fresh leaves by Ayurvedic physicians for the control of diabetes.